Disease burden, clinical management and unmet treatment need of patients with moderate to severe alopecia areata; consensus statements, insights, and practices from CERTAAE (Central/Eastern EU, Russia, Türkiye AA experts) Delphi panel - Rudnicka, Lidia; Trzeciak, Magdalena; Alpsoy, Erkan; Arenberger, Petr; Alper, Sibel; Benáková, Nina; Bobko, Svetlana; Borlu, Murat; Czarnecka Operacz, Magdalena; Engin, Burhan; Ergun, Tülin; Sağduyu, Ilgen Ertam; et al. (Frontiers in Medicine, 2024)
Objectives This study aims to update the understanding of Alopecia Areata (AA) in Poland, Czechia, Russia, and Türkiye, focusing on the disease burden, clinical management, and patient journey. It seeks to establish a consensus on optimal management strategies for AA in these regions. Methods A modified 2-round Delphi panel was conveyed with 23 Dermatologists (Russia; 4, Türkiye; 7, Poland; 6, and Czechia; 6). The Delphi questionnaire consisted of 61 statements and 43 questions designed to obtain an overall understanding of the perception and acceptance of available information regarding the care of patients with alopecia areata. Results The study revealed that moderate-to-severe AA significantly impacts patients’ and their families’ QoL, consistent with previous studies. AA was found to cause more substantial impairment when additional lesions appeared in visible areas besides the scalp. Work and productivity impairment were notably higher in adults with moderate-to-severe AA. Diagnostic consensus highlighted the importance of skin biopsies and trichoscopy, while the need for more practical severity scoring systems was emphasized. Current treatments, including topical therapies, corticosteroids, and systemic immune modifiers, were deemed insufficient, highlighting the unmet medical need. Conclusion The Delphi study underscores a significant disease burden and unmet medical needs in patients with moderate-to-severe AA. It highlights the necessity of access to novel treatments and further research to develop more effective therapies with a tolerable safety profile. The findings align with global research, emphasizing the psychosocial impact of AA and the need for standardized, effective treatment protocols.